A Mild Strategy for the Preparation of Phenols via the Ligand-Free Copper-Catalyzed O-Arylation of para-Toluenesulfonic Acid - Yong-Hao Tan, Bryan; Teo, Yong-Chua (Synlett, 2016)
A facile and simple ligand-free copper-catalyzed reaction to synthesize substituted phenols is reported. The reaction presumably proceeds via an O-arylsulfonate intermediate that is hydrolyzed to afford good to excellent yields of up to 88%. This protocol provides an alternative to existing reports which use strong hydroxide salts as the direct hydroxylation partner. Demonstrating a wide substrate scope and functional group tolerance, this protocol can also be applied to inexpensive and commercially available carboxylic acids to yield phenols.
Keywords: phenol; copper; ligand-free; water; p-toluenesulfonic acid